PEMANFAATAN MORINGA OLIEFERA DAN ESSENTIAL OIL MENJADI MASKER PEEL OFF KESEHATAN KULIT WAJAH DENGAN KONSEP ECOFRIENDLY - Samosir, Sri Rezeki; Elnovreny, Jane; Siagian, Hartika Samgryce; Mardiah, Ainun (Universitas Imelda Medan, 2024)
A peel-off mask cosmetic product has been made from the ethanol extract of the leaves of the Moringa oliefera plant. The research method is experimental. Moringa leaf extract was obtained by the maceration method using 75% ethanol solvent. The extract is divided into six formulations, namely FI (0.5%), FII (1%), FIII (1.5%) and FIV (0.5%), FV (1%), FVI (1.5%) . The formulation for making peel off mask products uses a mixture of green tea essential oils (FIV, FV, FVI). Evaluation of Peel Off mask product preparations consists of organoleptic tests, homogeneity tests, pH tests, Hedonic tests, Irritation tests, spreadability tests. Based on the results of organoleptic tests, non-essential oil preparations in FI have a yellow color, FII has a brown color, and FIII has a brown color, where all three formulations have the aroma of Moringa leaves, while the formulation with the addition of essential oil in FIV has a white color, FV has a brown color, and FVI Brown in color, all three formulations have the aroma of green tea essential oil. The homogeneity test results of all formulations have a homogeneous texture and have a pH of 7. The hedonic test uses 10 panelists to determine the panelists' level of preference. The hedonic test results for color are 40% FI, 50% FII, 60% FIII, 100% FIV, 90% FV and 90% FVI. The hedonic test for texture is 50% FI, 60% FII, 50% FIII, 80% FIV, 100% FV, and 90% FVI. The hedonic test for aroma obtained 20% FI, 40% FII, 50% FIII, 80% FIV, 90% FV and 90% FVI. The Moringa leaf extract peel off mask does not cause irritation to the skin and has a spreadability of around 3.9 – 6.2 cm.